Spatial Misallocation in Canada - Alam, M.; Emery, Herb (Canadian Journal of Regional Science / Revue canadienne des sciences régionales)

(untitled) (Canadian Regional Science Association / Association canadienne des sciences régionales, 2025)
Factor misallocation across firms has been well-documented and for Canada, it appears that spatial misallocation of labour and capital across regions may have important implications for national economic growth. Spatial misallocation hinders economic efficiency by preventing resources from being allocated to their most productive uses, thereby constraining growth. Using Canadian data from 2000 to 2018, we find that labour productivity increased by approximately 1% annually, while capital productivity declined by around 1% per year. This is concurrent with an increase in the spatial misallocation of labour and a decrease in the spatial misallocation of capital. We examine the factors correlated with these inefficiencies and find that production subsidies are positively associated with higher spatial misallocation of factors, suggesting that such subsidies may help sustain less productive firms, dampening national economic growth.